Pengaruh Implementasi Manajemen Kurikulum Merdeka dan Strategi Mengajar Guru terhadap Peningkatan Karakter Siswa di SMKN 1 Sangatta Utara - Halimatus Sa’diyah; Eko Nursalim; Muh Ibnu Faruk Fauzi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to determine the influence of the implementation of the Independent Curriculum management and teacher teaching strategies on improving student character at SMK Negeri 1 Sangatta Utara. This study was field research with a quantitative approach. Data collection techniques used questionnaires, observation, and documentation. The study population was all 230 11th-grade students at SMK Negeri 1 Sangatta Utara, with a sample of 115 respondents drawn using Suharsimi Arikunto's formula. Data analysis used multiple linear regression. The results showed that the implementation of the Independent Curriculum management had a significant effect on improving student character by 60.85%, while teacher teaching strategies had a 15.95% effect. The coefficient of determination (R²) of 0.768 indicates that the two independent variables together contributed 76.8% to student character improvement, while the remaining 23.2% was influenced by factors outside the study. Therefore, it can be concluded that the implementation of the Independent Curriculum management has a more dominant influence than teacher teaching strategies on student character development.